Pelatihan Komunikasi Terapeutik Berbasis Pathway Penyakit untuk Meningkatkan Kemampuan Edukasi Mahasiswa Keperawatan kepada Pasien dan Keluarga - Nixson Manurung (Cattleya Darmaya Fortuna, 2026)
Students have understood the theory of therapeutic communication and nursing science, but still struggle to connect the causes of diseases, physiological changes, nursing problems, interventions, and patient education in a simple explanation. To improve communication skills, clinical reasoning, disease pathway development, and students' confidence when providing education to patients and families. Socialisation, material provision, demonstration, case discussion, pathway development, role simulation, mentoring, pre-test, post-test, questionnaire, and practice observation. The article states that there is an increase in knowledge, the ability to create pathways, the use of simple language, empathetic attitudes, and skills in validating patient understanding. Program indicators were reported to be achieved, including 98% attendance, 85% post-test improvement, 90% ability to create pathways, and 80% therapeutic communication practice. Disease pathways are positioned as a learning medium that bridges basic nursing knowledge, clinical reasoning, and therapeutic communication, and it is recommended to be integrated into laboratory learning and clinical practice.